ALASAN AUSTRIA MENGELUARKAN KEBIJAKAN ANTI-FACE-VEILING ACT PADA TAHUN 2017 - Rahita Queenelya, Putu Cindy; Suwecawangsa, Adi Putra; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
This studypursuing to explain further the reasons of Austria in releasing the Anti-Face-Veiling Act 2017 with an exploratory qualitative method. The development of Islam in Austria has a complex twist. Austrian society increasingly questioned their religious freedom after the issuance of the Anti-Face-Veiling Act in 2017 that was officially enacted on October 1, 2017, and contains provisions prohibiting the use of clothing that covers the face from the hairline to the chin for Austrian people unless for several reason; medical and work-related clothing. This policy reaped a lot of confusion and protests from many parties. The Austrian Muslim community considers that the policy issued by the government is deliberately aimed at Muslim women who use niqab and burqa. This research then found the answer that the reason Austria issued the Anti-Face-Veiling Act policy was because of the raise of islamophobia in Austria’s society that based on several phenomenon.   Kata Kunci : Austria, Anti-Face-Veiling Act, Islamophobia